Salt and Nitric Oxide Inhibition Induced Hypertension: The Role of Prostacycline and 8-Isoprostane - Ilhan, Selcuk; Oktar, Suleyman; Sahna, Engin; Aksulu, Hakki Engin (Taylor & Francis Inc, 2011)
Renal prostacycline (PGI(2)) and oxidative stress are known to be important factors that effect the natriurezis and diuresis. 8-iso prostaglandin F-2 alpha (8-isoprostane), a member of F-2-isoprostanes, is formed from the nonenzymatic reaction of arachidonic acid and oxygen radicals in vivo and in vitro, and also it is a marker of oxidative stress in vivo. The aim of this study is to determine the role of renal PGI(2) and 8-isoprostane in a salt and nitric oxide (NO) inhibition-induced hypertension model. Rats were distributed equally among four groups (n = 6 per group). Control rats were given normal salt diet (0.32%); high-salt (HS) rats were given high salt diet (3.2%); NG-nitro-L-arginine (L-NNA) rats were given normal salt diet and 25 mg/kg L-NNA; HS+L-NNA rats were given high salt diet and 25 mg/kg L-NNA. Rats were placed in individual metabolic cages for 17 days. Systolic blood pressure (SBP) was measured at days initial, 7th and 14th. Urinary 8-isoprostane and PGI(2) levels were analyzed. Salt-loading alone did not change SBP values. The average SBP in L-NNA and HS+L-NNA groups were shown to significantly enhance compared to initial and day 7th in the same groups, respectively. The levels of 8-isoprostane in the HS+L-NNA group was significantly enhanced compared to the other groups. L-NNA or HS diet alone did not change the levels of 8-isoprostane compared to the control group. L-NNA alone did not change PGI(2) levels in urine compared to the control. PGI(2) levels in the HS, and the HS+L-NNA group was significantly higher compared to the control group. This study concluded that NOS inhibition plus salt-loading induced oxidative stress and increased renal PGI(2). Also, it is suggested that augmented oxidative stress may aggravate the hypertension. But the renal synthesis of PGI(2) is increased in order to augment the diuresis and natriuresis without the effect of blood pressure (BP).
Keywords: nitric oxide (NO); 8-isoprostane; prostacyclin; salt-loading; hypertension